From Scepticism to Nihilism: A Nihilistic Interpretation of Nāgārjuna’s Refutations - Shaoyong Ye (Journal of Indian Philosophy, 2019)
On the basis of Nāgārjuna’s works, especially the Mūlamadhyamakakārikā, this paper proposes a sceptic presupposition as the departure point of Nāgārjuna’s refutations. This presupposition invalidates perceptual knowledge, and thus the identities of existents (svabhāva) can only be deemed as referents assumed by concepts (nāman, vikalpa, etc.). Then the “confinement principle,” a theorem tacitly applied in Nāgārjuna’s arguments, is justified, i.e., any definition or description of a concept would necessarily confine its assumed referent to an invariable and isolated state. This principle enables Nāgārjuna to deduce contradictions between the static and isolated nature of the assumed referent, and the activity in which it must be involved. Notions of both a static identity and its activity are deep-rooted in all referential mental activities of sentient beings. Hence all concepts are found to be self-contradictory and therefore devoid of referents (niḥsvabhāva), namely, empty (śūnya). Thus, Nāgārjuna is refuting the whole intelligible world, and his position can be identified as epistemological nihilism—nothing within our ken can possibly be